In-situ visualizing atomic structural evolution during crystallization in ternary ZrCuAl bulk metallic glasses. (February 2019) - Wei, Xiaoya; Lan, Si; Wu, Zhenduo; Ohnuma, Masato; Shibayama, Tamaki; Watanabe, Seiichi; Zhou, Jie; Lu, Zhaoping; Ren, Yang; Wang, Xun-Li
Abstract: A well-designed experimental method has been presented to in-situ visualize the amorphous-to-crystalline phase transformation of two glass formers at the atomic-length scale in the supercooled liquid region using a high voltage electron microscopy (HVEM). Analysis of the HVEM high-resolution images, supported by the in-situ synchrotron diffraction, further confirms previous observations of distinctively different crystallization pathways in the two ZrCuAl alloys. Moreover, the HVEM results illustrate that isolated distributed nanocrystals with mutual orientation easily grew up from the Zr56 Cu36 Al8, an average glass former, which follows a classical crystallization pathway; while density population poorly ordered atomic clusters with large misorientation suspended the growth in the Zr46 Cu46 Al8, a good glass former, which might follow an unusual crystallization pathway. In addition, in-situ synchrotron diffraction measurements confirm that the Zr56 Cu36 Al8 alloy finally crystallized into an extended structure, in contrast, the final crystalline product of Zr46 Cu46 Al8 alloy possesses a damped structure. Our study provides a detailed microscopic understanding of the crystallization behaviors in the supercooled liquids, showing that the density population nucleation site with large misorientation and the confined final crystalline structure contribute to the stability of ZrCuAl supercooled liquids.